2010
DOI: 10.1111/j.1469-7610.2010.02228.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and the environment in the etiology of childhood anxiety

Abstract: Anxiety disorders are prevalent throughout childhood and adolescence. As such, identifying the factors and mechanisms that precede, maintain, or exacerbate anxiety disorders is essential for the development of empirically-based prevention and intervention programs. The current review focuses on child temperament (i.e., behavioral inhibition) and the child's environment, including parenting, child care, and peer relationships, as these factors have been linked to internalizing problems and anxiety diagnoses. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
200
2
12

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(225 citation statements)
references
References 163 publications
10
200
2
12
Order By: Relevance
“…In this way family environment would be conceptualised as a moderator of the child temperament -anxiety relationship. Finally, it has also been proposed that family environment might mediate the relationship between temperament and child anxiety (Degnan et al, 2010). For example, temperament might lead to more overinvolved parenting which might, in turn, lead to increased anxiety.…”
Section: Family Environment Bi and Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…In this way family environment would be conceptualised as a moderator of the child temperament -anxiety relationship. Finally, it has also been proposed that family environment might mediate the relationship between temperament and child anxiety (Degnan et al, 2010). For example, temperament might lead to more overinvolved parenting which might, in turn, lead to increased anxiety.…”
Section: Family Environment Bi and Anxietymentioning
confidence: 99%
“…In summary, although research has established that BI and family environment are associated with child anxiety, research including multiple risk factors remains scarce (Degnan et al, 2010). Furthermore, with the notable exception of the cross-sectional study by Shamir-Essakow et al (2005), previous research examining multiple risk factors has relied on questionnaire measures of temperament, family environment and anxiety.…”
Section: Summary and Hypothesesmentioning
confidence: 99%
“…Therefore, there is a need to identify factors associated with treatment success and failure, which can aid in improving intervention strategies. Both stable child characteristics and environmental (parent) factors are considered to be important in the etiology and maintenance of anxiety disorders (for a review see Degnan, Almas, & Fox, 2010). However, there is scant research on the role these factors may play in treatment outcomes for anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 The family environment represents one factor that is likely to be important in young children's lives. Indeed, extensive research has reported that family factors such as parenting, attachment and parental psychopathology, play a role in the etiology of child anxiety.…”
mentioning
confidence: 99%